CHALLENGES OF LIBRARY MANAGEMENT TO IMPROVE STUDENT READING - Connie CHAIRUNNISA; Istaryatiningtyas ISTARYATININGTYAS (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2018)
Generally, in Indonesia read the students in school remains low interest, facts proved of research results in some place SDN in the territory of the central Jakarta (2017) have that the interest publication low student, this have consequence to the poor awareness of the needs of reading consciousness children of school age distinguished, not yet considers read the needs of primer. Any research to see low interest read in schools easily to be in measuring instruments of the list visits students to the school library still very skimpy meal. Unisco on 2012 report that the interest of the Indonesia punctuation just reaching figures 0,001, does that mean every 1000 people there is only one person has an interest punctuation. Compare with everage index read developed countries residing in between figures 0,45 up to 0,62. Around the countries in the region Asiatic the spirit of spirit read the Indonesia pertained skimpy meal. Reality of this will happen when the apprehensive on the child’s and teenagers who will be next generation. The Low of interest will read influence on the quality of human resources lower when compared with other nation in the world. The management of the school’s library in optimize contribution, human material and the budget to achieve the purpose of libraries are still having various challenge, could not walk, so as expected . The challenge the derived from two aspect, namely, the aspect structural, in the sense of less attention from the school management obtains and aspects of technical urgently required by the school library, as human resources, means of infrastructure, and the budgeting.